Physico-chemical and health-promoting properties of dietary fibre powder from pink guava by-products - Ibrahim, Aida Hamimi (2009)
Fruit by-products and their residues are usually available in large quantities and although costly to dispose, are not fully exploited commercially for lack of research. The pink guava by-product dietary fibre posses the physic-chemical and health-promoting properties, potentially a new natural ingredient for the health food industry. The objectives of the study were to determine the dietary fibre composition of pink guava by-product, to develop dietary fibre powder and to evaluate the functional properties and health benefits of the dietary fibre powder. The processing wasters from the pink guava industry were analysed for dietary fibre content (soluble, insoluble and total) and dietary fibre composition (hemicelluloses, cellulose and lignin). The resultant dietary fibre powder (DFP) was analysed for dietary fibre content, proximate composition (caloric value, moisture content, fat, protein, and carbohydrate); structure, colour and functional properties (water- retention capacity (WRC), oil-retention capacity (ORC), swelling-capacity (SWC), and particle size distribution. Fructooligossaccharides were also identified in the DFP. The dietary powder was evaluated for its health-promotion properties (total antioxidant and polyphenol contents, prebiotic and hypocholestrolemic effects). Pink guava by-products were found to have high total dietary fibre content (68.4 -78.8% dry matter) with high proportion of insoluble fibres. The types of insoluble fibres determined were cellulose (25-44% dry matter), hemicelluloses (12 – 25 % dry matter) and lignin (19 – 46 % dry matter). On the other hand, soluble fibre represents about 3.4% - 4.4 % dry matter of total dietary fibres. The prepared powder had a high total dietary fibre content (56.6% - 76.1% DM) and almost similar SDF: IDF ratios with cereal brans, and low caloric value (97.1 – 249.1 kcal/100 g). The DFP was light brown in colour with scale type structure. Due to their water – retention ability (3.75 – 12.17 g of water/ g of fibre), oil – retention (2.20 -6.88 g of fibre) and swelling (11.8 – 14.2 mL of water/g of fiber DM), the DFP may be used not only for dietary fibre enrichment and reduction of energy value, but also as functional ingredients in many food products. This study has shown that DFP of pink guava by – product contained fructooligosaccharides (FOS), known as prebiotic agent. A full separation of all FOS components (fructose, sucrose, 1-ketose and nytose) was achieved for dietary fibre powder. This product was found high in antioxidant activities (52 – 91.4 % AOA), radical scavenging effects (85.4 – 91.7 %) and total phenolic content (156 – 227.6 FAE mg/g). The study demonstrates that the dietary fibre powder is prebiotic food due to evident that the mesophilic bacteria decreased and bifidobacteria increased in vivo and in vitro conditions. It was evident that the dietary fibre powder had very pronounced hypocholesrolemic effects as it could significantly (p< 0.05) decrease the levels of serum total cholesterol (43 %) and LDL (51%) in rats. The dietary fibre powder from pink guava by-products was identified to have high antioxidant activity, prebiotic and hypocholestrolemic effects, the health- promotion properties that could boost its potential as functional ingredient for food industry.